Factors influencing purchase intention based on facebook advertising: DAS / Akmal Aini Othman ... [et al.] - Othman, Akmal Aini; Dahlan, Jaslin Md; Mat Din, Syaidatul Zarina; Zainuddin, Noor Azrin; Shukri, Akmal Shakir (UiTM Cawangan Johor, 2019)
Nowadays, growth of social media has become significant to customers to make purchasing through Facebook commerce. However, little studies about Facebook commerce in the beauty industry compared to other industries in Malaysia. DAS uses Facebook commerce as a strategy to make transaction with customer. The purpose of the study is to determine the factors and relationship of purchase intention towards DAS Facebook commerce. Therefore, the study is conducted to identify factors on purchase intention towards Facebook commerce. A survey was conducted using convenience sampling and 100 respondents answered the questionnaire. This study used quantitative method. Overall, the result shows that all of the variables have positive relationship with the dependent variables, but only three of them are significant for this study. Thus this study is expected to help DAS to improve the Facebook Commerce as their platform to sell the products and services.